How do you solve -\frac { 1} { 3} ( x + 5) \geq - \frac { 4} { 9} ( x - 2)?
2 Answers
Nov 5, 2017
x ∈ [23;+∞>
Explanation:
multiplying by 27 because 3*9=27
then
distributive property
transposing terms
finally
then x ∈ [23;+∞>
Nov 5, 2017
Explanation:
"to eliminate the fractions multiply both sides of the "
"inequation by the "color(blue)"lowest common multiple"
"of 3 and 9"
"the lowest common multiple of 3 and 9 is 9"
cancel(9)^3xx-1/cancel(3)^1(x+5)>=cancel(9)^1xx-4/cancel(9)^1(x-2)
rArr-3(x+5)>=-4(x-2)
"distributing brackets gives"
-3x-15>=-4x+8
"add "4x" to both sides"
-3x+4x-15>=cancel(-4x)cancel(+4x)+8
rArrx-15>=8
"add 15 to both sides"
xcancel(-15)cancel(+15)>=8+15
rArrx>=23" is the solution"